Pirolisis Kayu Ketapang (Terminalia Catappal) Menjadi Bio-Oil Menggunakan Katalis NiMo/Lempung - Afria Anggreini; Syaiful Bahri; Khairat Khairat (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Recently, the avaibility of petroleum fuels is became limited. It is because the petroleum fuels was not balanced with the community consumption to petroleum fuels is very high. To overcome these problems needed alternative energy sources is the use of renewable biomass into bio-oil. Biooil is produced from biomass through pyrolysis. The purpose of this reseacrh is to produce biooil from ketapang wood, determine the effect of the impregnation percentage of NiMo metal, determine the effect of the catalyst weight, the physical and chemical characteristics of bio-oil. Pyrolysis was using 50 grams ketapang wood, 500 ml silinap and NiMo/Lempung catalyst withvariations of the impregnation percentage of NiMo metal 0%, 1%, 2%, 3% and the variation weight of catalyst NiMo/Lempung 3%, 4% and 5% of the biomass with a stirring speed of 300 rpm and a temperature of 320ºC for 120 minutes. In this research, the highest yield on the variation of the impregnation percentage of metal 1% and weight of catalyst 5% of the biomass amounted to 77,616%. Characteristics of bio-oil obtained were density 0,924 gr/ml, viscosity 2,510 cSt, acid number 76,781 mg NaOH/gr sample, and the flash point 500C. The results of GC-MS analysis, thedominant chemical components in the bio-oil were cyclohexanone (5,53%); heptadecane (4,17%); 1-propene, 2-methyl-,trimer (3,18%); 1-tetradecene (CAS) n-tetradec-1-ene (2,43%) serta octadecane (CAS) n-octadecane (2,21%).Keywords : Bio-oil, catalyst NiMo/Lempung, ketapang wood